Brassinosteroid-mediated stress tolerance in Arabidopsis shows interactions with abscisic acid, ethylene and salicylic acid pathways - Divi, Uday K (BioMed Central, 2010)
BACKGROUND: Brassinosteroids (BRs) play crucial roles in plant development and also promote tolerance to a range of abiotic stresses. Although much has been learned about their roles in plant development, the mechanisms by which BRs control plant stress responses and regulate stress-responsive gene expression are not fully known. Since BR interacts with other plant hormones, it is likely that the stress tolerance conferring ability of BR lies in part in its interactions with other stress hormones. RESULTS: Using a collection of Arabidopsis mutants that are either deficient in or insensitive to abscisic acid (ABA), ethylene (ET), jasmonic acid (JA) and salicylic acid (SA), we studied the effects of 24-epibrassinloide (EBR) on basic thermotolerance and salt tolerance of these mutants. The positive impact of EBR on thermotolerance in proportion to wild type was evident in all mutants studied, with the exception of the SA-insensitive npr1-1 mutant. EBR could rescue the ET-insensitive ein2 mutant from its hypersensitivity to salt stress-induced inhibition of seed germination, but remained ineffective in increasing the survival of eto1-1 (ET-overproducer) and npr1-1 seedlings on salt. The positive effect of EBR was significantly greater in the ABA-deficient aba1-1 mutant as compared to wild type, indicating that ABA masks BR effects in plant stress responses. Treatment with EBR increased expression of various hormone marker genes in both wild type and mutant seedlings, although to different levels. CONCLUSIONS: These results together indicate that the redox-sensitive protein NPR1 (NONEXPRESSOR OF PATHOGENESIS-RELATED GENES1), a master regulator of SA-mediated defense genes, is likely a critical component of EBR-mediated increase in thermotolerance and salt tolerance, but it is not required for EBR-mediated induction of PR-1 (PATHOGENESIS-RELATED1) gene expression; that BR exerts anti-stress effects independently as well as through interactions with other hormones; that ABA inhibits BR effects during stress; and that BR shares transcriptional targets with other hormones.